Pengetahuan Ibu dan Kepatuhan Ibu tentang Penggunaan Kontrasepsi di Masa Pandemi - Desi Ekawati; Retno Heru Setyorini (Sekolah Tinggi Ilmu Kesehatan Akbidyo, 2023)
ABSTRACTBackground: The world's population continues to grow, Indonesia is also predicted in 2025-2035 to be the fourth most populous country in the world. For this reason, it is necessary to control the rate of population growth through the family planning program using contraception. During the pandemic, it had several impacts, especially for the Family Planning (KB) program, namely: a decrease in family planning participants. Ultimately it will affect family planning services and membership. Family planning participants during a pandemic were afraid to make repeat visits because of their limited knowledge of family planning during a pandemic.Research objectives for the relationship between mother's knowledge about contraception and adherence to contraceptive use during the pandemic.Subjects and Methods This research uses non-experimental research with an observational research design that aims to analyze a relationship between variables. This type of research uses cross sectional. The sampling technique in this study was simple random sampling. The subjects in this study were mothers who used contraception in Delanggu Village as many as 55 acceptors.Results: Based on the research, it can be found that out of 55 respondents, the majority of respondents have knowledge about contraceptive use in the good category, namely 26 respondents (47.48%). 30 respondents (54.5%) were obedient in using contraception, it was found that there was a significant relationship between mothers' knowledge about contraceptive use and adherence to contraceptive use during a pandemic with a p value = <0.001.Conclusion: Mother's knowledge of contraceptive use during a pandemic is good, adherence to contraceptive repeat visits during a pandemic is good and there is a significant relationship between maternal knowledge and maternal compliance in contraceptive services (p <0.001).Keywords: contraception, pandemic, compliance, knowledge, Covid19